2020
DOI: 10.7454/proust.v3i1.83
|View full text |Cite
|
Sign up to set email alerts
|

Support for Palestinian among Indonesian Muslim: Religious identity and solidarity as reasons for e-petition signing

Abstract: A petition is a form of collective action urging the government or a public entity to resolve a specific situation. There is inconsistency between previous research on whether religious or political identity is more likely to lead to radical or peaceful actions, especially in terms of how feelings of solidarity relate to religious-political issues. This study examines the reasons Indonesians signed e-petitions supporting Palestine. Data were collected from the comment sections of e-petitions supporting Palesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Previous studies have demonstrated why people supported and joined collective actions and endorsed solidarity (Adra, Li, & Baumert, 2020; Bäck, Bäck, & Sivén, 2018; Dixon et al, 2016; Mashuri et al, 2022; Ouch & Moradi, 2022; Shadiqi, Muluk, & Milla, 2018, 2020). Among others, it is because of the shared engagement with others and perceptions that such action is able to boost social change (Bäck et al, 2018; Dixon et al, 2016).…”
Section: Common Identity and Internal Problems During The Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated why people supported and joined collective actions and endorsed solidarity (Adra, Li, & Baumert, 2020; Bäck, Bäck, & Sivén, 2018; Dixon et al, 2016; Mashuri et al, 2022; Ouch & Moradi, 2022; Shadiqi, Muluk, & Milla, 2018, 2020). Among others, it is because of the shared engagement with others and perceptions that such action is able to boost social change (Bäck et al, 2018; Dixon et al, 2016).…”
Section: Common Identity and Internal Problems During The Pandemicmentioning
confidence: 99%
“…On the other hand, abundant studies have shown that the less people feel connected to others, the more ignorant they are to others' problems and suffering (e.g., Mashuri, Burhan, & van Leeuwen, 2012; Van Leeuwen & Mashuri, 2012, 2013). Some Muslims in Indonesia will care more about what is happening in the Middle East than in Ukraine or Ethiopia because of the concept of brotherhood in Islam (Shadiqi et al, 2020). Compared to other ASEAN countries, the people of the Pacific Islands nations have more drive to solve the problem in West Papua as they have a race similarity to Melanesians (Blades, 2020; Wangge & Lawson, 2021).…”
Section: Common Identity and Internal Problems During The Pandemicmentioning
confidence: 99%
“…Kedua negara ini telah berselisih sejak negara Israel berdiri di tanah Palestina sejak 1948 (Bachtiar, Razak, & Zakaria, 2021;Nabilah et al, 2022;Zhafira, 2023). Secara kolektif, terdapat keyakinan bahwa Israel telah melanggar hak asasi manusia yang menghambat kemerdekaan Palestina, di mana keyakinan ini didasari oleh kesamaan identitas agama dan solidaritas antara Indonesia dan Palestina dalam melawan penjajah (Shadiqi, Muluk, & Milla, 2020). Kabar dari adanya museum ini menjadi perbincangan dunia maya hingga dijadikan sebagai segmen diskusi di sebuah stasiun televisi swasta (Catatan Demokrasi, 2022).…”
Section: Pendahuluanunclassified